Benchmarking Agricultural Research Indicators Across Asia–Pacific - Flaherty, Kathleen; Stads, Gert-Jan; Srinivasacharlyulu, Attaluri (International Food Policy Research Institute, 2013)
New quantitative evidence presented in this report demonstrates that total public agricultural R&D spending in Asia–Pacific increased by 50 percent, from $8.2 billion in 1996 to $12.3 billion in 2008 (in 2005 PPP prices). Most of this growth was driven by the region’s low- and middle-income countries, whereas growth in the region’s high-income countries stagnated. In fact, growth in public agricultural R&D spending in the region’s low- and middle-income countries has outpaced growth in all other developing regions around the world since the 1980s. As a result, the region has increasingly raised the profile of its contribution to global agricultural R&D.